The Kate in between - Swinarski, Claire (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
Twelve-year-old Kate becomes the face of an anti-bullying movement after a heroic act goes viral, but her world is turned upside-down when the truth about her involvement is revealed.